Diagnostic accuracy of 1p/19q codeletion tests in oligodendroglioma: A comprehensive meta‐analysis based on a Cochrane systematic review. (3rd March 2022) - Brandner, Sebastian; McAleenan, Alexandra; Jones, Hayley E.; Kernohan, Ashleigh; Robinson, Tomos; Schmidt, Lena; Dawson, Sarah; Kelly, Claire; Leal, Emmelyn Spencer; Faulkner, Claire L.; Palmer, Abigail; Wragg, Christopher; et al.
Abstract: Codeletion of chromosomal arms 1p and 19q, in conjunction with a mutation in the isocitrate dehydrogenase 1 or 2 gene, is the molecular diagnostic criterion for oligodendroglioma, IDH mutant and 1p/19q codeleted. 1p/19q codeletion is a diagnostic marker and allows prognostication and prediction of the best drug response within IDH‐mutant tumours. We performed a Cochrane review and simple economic analysis to establish the most sensitive, specific and cost‐effective techniques for determining 1p/19q codeletion status. Fluorescent in situ hybridisation (FISH) and polymerase chain reaction (PCR)‐based loss of heterozygosity (LOH) test methods were considered as reference standard. Most techniques (FISH, chromogenic in situ hybridisation [CISH], PCR, real‐time PCR, multiplex ligation‐dependent probe amplification [MLPA], single nucleotide polymorphism [SNP] array, comparative genomic hybridisation [CGH], array CGH, next‐generation sequencing [NGS], mass spectrometry and NanoString) showed good sensitivity (few false negatives) for detection of 1p/19q codeletions in glioma, irrespective of whether FISH or PCR‐based LOH was used as the reference standard. Both NGS and SNP array had a high specificity (fewer false positives) for 1p/19q codeletion when considered against FISH as the reference standard. Our findings suggest that G banding is not a suitable test for 1p/19q analysis. Within these limits, considering cost per diagnosis and using FISH as a reference, MLPA was marginally more cost‐effective than other tests, although these economic analyses were limited by the range of available parameters, time horizon and data from multiple healthcare organisations. Abstract : In this summary of a Cochrane review, we analysed the diagnostic accuracy of 1p/19q codeletion tests in oligodendroglioma, to establish the most sensitive, specific and cost‐effective techniques. Fluorescent in situ hybridisation (FISH) and polymerase chain reaction (PCR)‐based loss of heterozygosity (LOH) test methods were considered as reference standards. Next‐generation sequencing and single nucleotide polymorphism arrays were found to have a high specificity. We found no difference in the hazard ratio for overall survival between studies, using two different techniques, PCR‐based LOH and FISH.